Colonizing Hawai'i : the cultural power of law - Merry, Sally Engle, 1944-2020 (Princeton University Press, 2000)
How does law transform family, sexuality, and community in the fractured social world characteristic of the colonizing process? The law was a cornerstone of the so-called civilizing process of nineteenth-century colonialism. It was simultaneously a means of transformation and a marker of the seductive idea of civilization. Sally Engle Merry reveals how, in Hawai'i, indigenous Hawaiian law was displaced by a transplanted Anglo-American law as global movements of capitalism, Christianity, and imperialism swept across the islands. The new law brought novel systems of courts, prisons, and conceptions of discipline and dramatically changed the marriage patterns, work lives, and sexual conduct of the indigenous people of Hawai'i.
Keywords: USA -- Government; Hawaiians -- Government relations.; Hawaiians -- Legal status, laws, etc.; Hawaiians -- Politics and government.; Customary law -- Hawaii.; United States -- Foreign relations -- Hawaii.; Hawaii -- Foreign relations -- United States.; États-Unis -- Relations extérieures -- Hawaii.; Hawaii -- Relations extérieures -- États-Unis.; Hawaïens -- Relations avec l'État.; Droit coutumier -- Hawaii.; 86.06 ethnological jurisprudence.; SOCIAL SCIENCE -- Anthropology -- General.; Customary law; Hawaiians -- Government relations; Hawaiians -- Politics and government; Diplomatic relations; Hawaii; United States; Außenpolitik; Geschichte; Kolonialismus; Politik; Rechtssystem; Recht.; Rechtsstelsels.; Hawaii.; United States of America.; Law.; Hawaiiens -- Relations avec l'État.; Hawaiiens -- Statut juridique.; Hawaiiens -- Politique et gouvernement.; Droit coutumier -- États-Unis -- Hawaii.; Afghanistan.; Baker, James.; Blackwell, David.; Caucus-race.; Chappaquiddick.; Durkheim, Emile.; Ford, Gerald.; Gephardt, Richard.; Hart, Gary.; Hodgson, Godfrey.; Houston Chronicle.; Iran hostage crisis.; Jordan, Hamilton.; Joslyn, Richard.; Kemp, Jack.; Kennedy, Robert.; Lydon, Christopher.; McGovern-Fraser commission.; Nevada primary.; Ohio primary.; Opus (penguin).; Reagan, Ronald.; Sanford, Terry.; ambiguity.; approval voting.; brokered convention.; campaign effects.; campaign effort.; character traits.; contagion.; conventions.; cue-taking.; deathwatch coverage.; delegates.; environmental protection.; expectations.; feeling thermometer.; foreign policy.; government services.; horse race.; information.; labor unions.; liberalism scores.; logit analysis.; media use.; momentum.; nuclear power.; paradox of voting.; party identification.; projection.; representation.; rules.; History (form)